Iron Homeostasis in Tissues Is Affected during Persistent Chlamydia pneumoniae Infection in Mice. (13th June 2017) - Edvinsson, Marie; Tallkvist, Jonas; Nyström-Rosander, Christina; Ilbäck, Nils-Gunnar
Abstract : Chlamydia pneumoniae (C. pneumoniae) may be a mediator in the pathogenesis of atherosclerosis. For its growth C. pneumoniae depends on iron (Fe), but how Fe changes in tissues during persistent infection or affects bacterial replication in tissues is unknown. C. pneumoniae -infected C57BL/6J mice were sacrificed on days 4, 8, 20, and 40. Mice had bacteria in the lungs and liver on all days. Inflammatory markers, chemokine Cxcl2 and interferon-gamma, were not affected in the liver on day 40. The copper (Cu)/zinc (Zn) ratio in serum, another marker of infection/inflammation, increased on day 4 and tended to increase again on day 40. The Fe markers, transferrin receptor (TfR), Hepcidin (Hamp1), and ferroportin 1 (Fpn1), increased in the liver on day 4 and then normalized except for TfR that tended to decrease. TfR responses were similar to Fe in serum that increased on day 4 but tended to decrease thereafter. In the liver, Fe was increased on day 4 and also on day 40. The reappearing increases in Cu/Zn on day 40 concomitant with the increase in liver Fe on day 40, even though TfR tended to decrease, and the fact that viable C. pneumoniae was present in the lungs and liver may indicate the early phase of activation of recurrent infection.